2013
DOI: 10.1016/j.pharmthera.2013.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics: A novel therapeutic approach for the treatment of Alzheimer's disease

Abstract: Alzheimer’s disease (AD) is the most common type of dementia in the elderly. It is characterized by the deposition of two forms of aggregates within the brain, the amyloid β plaques and tau neurofibrillary tangles. Currently, no disease-modifying agent is approved for the treatment of AD. Approved pharmacotherapies target the peripheral symptoms but they do not prevent or slow down the progression of the disease. Although several disease-modifying immunotherapeutic agents are in clinical development, many have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 205 publications
(261 reference statements)
1
74
0
9
Order By: Relevance
“…Abbreviations: a-tub, a-tubulin; IR, immunoreactivity; OLE, oleuropein aglycone; QC, glutaminyl cyclase; wt, wild type. * p < 0.05, ** p < 0.01, *** p < 0.001. novel promising therapeutic strategy to treat AD (Adwan and Zawia, 2013). Therefore, the search of a causative link of the beneficial effects of OLE on AD-like pathology of 12-month-old TgCRND8 mice brought us to investigate whether OLE affected the level of histone acetylation in the brains of our wt and Tg mice.…”
Section: Ole Induces Histone Acetylation In 12-month-old Tgcrnd8 Micementioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviations: a-tub, a-tubulin; IR, immunoreactivity; OLE, oleuropein aglycone; QC, glutaminyl cyclase; wt, wild type. * p < 0.05, ** p < 0.01, *** p < 0.001. novel promising therapeutic strategy to treat AD (Adwan and Zawia, 2013). Therefore, the search of a causative link of the beneficial effects of OLE on AD-like pathology of 12-month-old TgCRND8 mice brought us to investigate whether OLE affected the level of histone acetylation in the brains of our wt and Tg mice.…”
Section: Ole Induces Histone Acetylation In 12-month-old Tgcrnd8 Micementioning
confidence: 99%
“…We also checked the level of histone acetylation in the oldest treated and untreated animals to ascertain whether the protective effects of OLE supplementation also involved epigenetic modifications. In fact, recent data indicate that epigenetic changes are implicated in learning and memory (Graff et al, 2012) and these modifications have been suggested as potential targets for AD therapeutics (Adwan and Zawia, 2013). Accordingly, we investigated the functional effects of OLE in aged animals by assessing in brain slices whether its administration in vitro was able to counteract dysfunctions of transgene-induced long-term potentiation (LTP) in the CA1 hippocampal area.…”
Section: Introductionmentioning
confidence: 99%
“…In general, DNA methylation is associated with blockade of gene expression (14). Several lines of evidence now demonstrate that aberrant DNA methylations of genes in AD are implicated in the initiation and progression of AD (32). Neprilysin (NEP), a zincdependent metallopeptidase, serves as the major physiological Aβ-degrading enzyme (9).…”
Section: Inhibition Of Akt/nf-κb Signaling By Cur Is Associated With mentioning
confidence: 99%
“…Recent literature shows that epigenetic regulations could stand as a valuable therapeutic strategy for AD [148]. Particularly, several studies report acetylation dysregulations associated with pathological markers of this disease.…”
Section: Ad and Related Diseasesmentioning
confidence: 99%